Tactics and Strategies for the Synthesis of Cereblon Ligands - Villemure, Elisia; Wang, Yong; Zhou, Yuebiao; Wong, Alice R.; Nilewski, Christian (Synthesis, 2024)
Targeted protein degradation (TPD) has emerged as an important strategy to target disease-relevant proteins that were previously considered difficult to drug or even undruggable. Cereblon (CRBN) plays an outsized role in TPD as a preferred degradation-inducing effector protein for several reasons, including its anticipated broad protein substrate scope and its ligandability with drug-like small molecules. Notably, CRBN-based molecular glue degraders (MGDs) and proteolysis targeting chimeras (PROTACs) have shown success in clinical trials and, in some cases, as approved drugs. Thus, the interest in CRBN ligands within the pharmaceutical industry and academia has increased dramatically in recent years, highlighting the need for robust synthetic approaches towards them. This short review summarizes tactics and strategies to synthesize CRBN ligands, including the most recent developments in the field. Particular emphasis is put on the construction and direct functionalization of key CRBN binding motifs such as glutarimides and dihydrouracils.1 Introduction2 Cereblon Ligands with Glutarimide Binding Motif3 Cereblon Ligands with Dihydrouracil Binding Motif4 Cereblon Ligands with Other Binding Motifs5 Conclusions and Outlook
Keywords: IMiDs; glutarimide; dihydrouracil; molecular glues; bivalent degraders; cereblon; drugs; medicinal chemistry